Breitbandige Frequenzweichen für die Parallelisierung von Millimeterwellen-Messtechnik - Klaus Boes, Florian (Karlsruher Forschungsberichte aus dem Institut für Hochfrequenztechnik und Elektronik, 2021)
This work describes the novel use of broadband continuous diplexers that could be integrated into on-wafer probes to parallize millimeter wave on-wafer measurement equipment. A model-based method for the efficient design of diplexers with a large number of adjustable parameters allows the realization of a DC - 110 GHz - 170 GHz diplexer for the first time.